Orientation‐selective functional magnetic resonance imaging adaptation in primary visual cortex revisited - Weigelt, Sarah (Hum Brain Mapp, 2011)
The processing of orientations is at the core of our visual experience. Orientation selectivity in human visual cortex has been inferred from psychophysical experiments and more recently demonstrated with functional magnetic resonance imaging (fMRI). One method to identify orientation‐selective responses is fMRI adaptation, in which two stimuli—either with the same or with different orientations—are presented successively. A region containing orientation‐selective neurons should demonstrate an adapted response to the “same orientation” condition in contrast to the “different orientation” condition. So far, human primary visual cortex (V1) showed orientation‐selective fMRI adaptation only in experimental designs using prolonged pre‐adaptation periods (∼40 s) in combination with top‐up stimuli that are thought to maintain the adapted level. This finding has led to the notion that orientation‐selective short‐term adaptation in V1 (but not V2 or V3) cannot be demonstrated using fMRI. The present study aimed at re‐evaluating this question by testing three differently timed adaptation designs. With the use of a more sensitive analysis technique, we show robust orientation‐selective fMRI adaptation in V1 evoked by a short‐term adaptation design. Hum Brain Mapp, 2012. © 2011 Wiley Periodicals, Inc.